Just Like a Woman: Gender Role Stereotypes in Forensic Psychiatry - Ali, Saima; Adshead, Gwen (Frontiers in Psychiatry, 2022)
The relationship between violence, gender and mental health is a complex one which is yet to be fully understood. Gender role stereotypes are social constructs that can powerfully influence and regulate human behaviour, including violence; and so it is likely that they also influence the nexus of violence management and mental health which is at the core of forensic psychiatry. In this article, we examine how gender role stereotypes might influence the practice of forensic psychiatry: specifically, in relation to women as violent offenders, as patients in secure psychiatric care and as clinicians working in forensic settings. We identify areas of development in women’s forensic mental health services, and examine whether patriarchal influences and gender role stereotypes may have inadvertently impacted upon these changes. We also consider whether these changes may maintain pre-existing barriers to treatment for both men and women.